Contents of Interrogative Speech Act of Indonesian Language Teachers in Teaching Processes at Senior High School of Muhammadiyah Wonosobo - Guntur Sakti Dewangga (Journal Educational of Indonesia Language, 2022)
This study aims to reveal the contents of interrogative speech act of Indonesian language teachers in teaching processes at Senior High School of Muhammadiyah Wonosobo. This study was qualitative research. The subjects were four Indonesian teachers at Senior High School of Muhammadiyah Wonosobo. The object was the speech of the four Indonesian teachers in their teaching processes. The data were collected by recording, interviews, and through observations, and was analyzed by using the content analysis. The results are as follows. First, the most frequently used is conceptual question, because in teaching the teachers ask more about the concept of a particular material. Second, empirical questions appear a lot in early learning activities. Third, the values questions does not appear much in learning.